ANALISIS PENGARUH RASIO CAMELS TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2012 (Students' Journal of Accounting and Banking, 2014)
This study was conducted to examine the effect of ratio CAMELS (Capital Adequacy Ratio, Return On risked Assets, Net Profit Margin, Return on Assets, Loan to Deposits Ratio and Interest Rate Risk on stock returns.The population used in this study are listed on the Stock Exchange Bank during the years 2010-2012. The sampling technique used was purposive sampling. Obtained a total sample of 24 banking companies. The data analysis technique used is multiple linear regression and hypothesis testing using the t-statistic for testing the partial regression coefficients and F-statistics to test the significance of the effect together with a significance level of 5%. It also performed classical assumption which include normality test, multicollinearity, heteroscedasticity and autocorrelation test.Analysis results can be concluded that: variable Capital adequacy ratio, Return on risked assets (RORA) and Net profit margin (NPM) has no significant effect on stock returns, while the variable Return on Assets, Loan to deposite and Interest Rate Risk ratio has a positive effect on stock returns.Keywords: Capital Adequacy Ratio, Return On Risked Assets, Net Profit Margin, Return on Assets, Loan to Deposits Ratio, Interest Rate Risk and stock returns